2015
DOI: 10.5144/0256-4947.2015.303
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of antiretroviral therapy in an adult HIV program: a 10-year retrospective cohort study in Kano, Nigeria

Abstract: BACKGROUNDTreatment outcomes from HIV/AIDS programs in resource-limited settings mostly describe short-term follow-up. We report 10-year treatment outcomes in an HIV clinic in Kano, Nigeria.METHODSUsing paper medical charts, the authors conducted a retrospective cohort study of patients that initiated ART from June 1, 2004 to December 31, 2007, and were followed up until June 30, 2014. The authors abstracted data from patient case files and did a time-to-event analysis on ART failure and loss to follow-up, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
9
3
Order By: Relevance
“…Over the past decade, there has been an unparalleled effort to provide access to antiretroviral therapy (ART) for HIV-infected individuals in sub-Saharan Africa, the region with the highest HIV burden [2]. In Sub-Saharan Africa, observations on effectiveness of ART showed encouraging results despite concerns in durability of therapeutic response [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, there has been an unparalleled effort to provide access to antiretroviral therapy (ART) for HIV-infected individuals in sub-Saharan Africa, the region with the highest HIV burden [2]. In Sub-Saharan Africa, observations on effectiveness of ART showed encouraging results despite concerns in durability of therapeutic response [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This 12-month retention rate is comparable to the 77% summarized retention in a meta-analysis using 2008 to 2013 LMIC data [38]. Few sub-Saharan African studies have reported data on longterm ART outcomestwo from Nigeria (ten-and seven-year follow-up), one from Uganda (ten-year follow-up), one from Zimbabwe (ten-year follow-up), one from Mozambique (nineyear follow-up) and one from South Africa (twelve-year followup) [23][24][25][26][27][28]. These studies show mixed results, with retention ranging from 37% to 83%, mortality from 1% to 24% and LTF from 5% to 51%; our observed ten-year 18.5% mortality and 28.8% LTF from the initiating clinic lie within these ranges "Yes, they give me a counselling.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has investigated the short-and medium-term clinical outcomes of people on ART and these studies demonstrate favourable treatment outcomes for cohorts in low-and middle-income countries (LMICs) [11][12][13][14][15][16][17][18][19][20][21][22]. More recently, several studies in low-resource settings have published longer term outcomes [23][24][25][26][27]; however, in South Africa, apart from two longer term studies [17,28], little is yet known about treatment outcomes beyond the first five years on ART in this context and retention-in-care remains suboptimal [29]. Even less is known about the experiences and perceptions of people who have been on treatment since the start of the programme and how these may have changed as the dramatic effects of ART became commonplace.…”
Section: Introductionmentioning
confidence: 99%
“…There are several definitions of loss to follow up on ART [30] which vary across different programs and studies [31] but in this study, a patient is declared loss to follow up if 90 days after the last missed clinic appointment, all efforts to trace and return the patient to service has failed [27]. Lost to follow-up is a major challenge that hinders the success of antiretroviral treatment [32] and it is the major cause of attrition from ART services. In sub-Saharan African countries, rates of loss to follow up vary as exhibited in the two studies in Nigeria and the study in 22 Sub-Saharan African countries.…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan African countries, rates of loss to follow up vary as exhibited in the two studies in Nigeria and the study in 22 Sub-Saharan African countries. In another systemic review of patient retention following ART initiation in Sub-Saharan African countries, it was evident that 1 year after initiation, approximately 25% of patients were no longer in cares, with loss to follow up figures escalating to 40% after 2 years [32]. However, it is reasonable to think that a patient lost to follow up may belong to any of the following categories: death, change of residence, self-transfer to other facilities without the knowledge of the treatment facility.…”
Section: Discussionmentioning
confidence: 99%